The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.18502/kss.v3i5.2351
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive Education in Indonesia: Equality Education Access for Disabilities

Abstract: Based on data from the World Bank, one out of ten poor people around the world is the disabled. Poverty experienced by the disabled is a direct and indirect result of the exclusion and marginalization of people with disabilities because of the stigma and prejudices about disability. One of the stigma and prejudice on people with disabilities arise in the educational setting. The United Nations [UN] report showed that 90 % of all children with disabilities in developing countries still do not attend school, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 0 publications
0
17
0
1
Order By: Relevance
“…For example, a 2009 decree (Decree of the Minister of Education No 70-2009) stated that every district should have an inclusive high school and that every sub-district should have one inclusive primary and one inclusive secondary school. Block grants were given to support these schools [For detailed analysis of the development and range of policies see (Wibowo & Muin, 2018)].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a 2009 decree (Decree of the Minister of Education No 70-2009) stated that every district should have an inclusive high school and that every sub-district should have one inclusive primary and one inclusive secondary school. Block grants were given to support these schools [For detailed analysis of the development and range of policies see (Wibowo & Muin, 2018)].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, in Indonesia, it is also observed that there are still governments that are less serious in focusing on inclusive education policies for people with disabilities, so this needs to be handled seriously (Ratnaningsih, Arhasy, & Hidayat, 2015). Furthermore, inclusive education in Indonesia is also observed as not fulfilling the concepts and guidelines presented, such as teacher qualifications, facilities and infrastructure, as well as family and community support, so many obstacles are faced in their implementation (Oktadiana & Wardana, 2019;Wibowo & Muin, 2018). However, efforts have been intensified by governments to respond to their educational rights through regulations and their implementation (Notoprayitno & Jalil, 2019).…”
Section: Inclusive Education Policy For Person With Disabilitiesmentioning
confidence: 99%
“…A few studies in support of the inclusiveness of people with disabilities are considerable, and it includes providing all services and access (Kumar, 2017;Roslina & Rahayu, 2019;Wibowo & Muin, 2018), focus on education and health services (Tigere & Moyo, 2019;van Nguyen, Do, Le, & Mai, 2018;Wiesel, Whitzman, Gleeson, & Bigby, 2019), involved in the political contexts (Boonyaruttanasoontorn, 2019;Halder & Argyropoulos, 2019;Kauffman & Anastasiou, 2019), opportunities for career development and employment (Boeltzig-Brown, 2017;Harry, 2020), and also, access and assistance support in technology (Sprunt, Deppeler, Ravulo, Tinaivunivalu, & Sharma, 2017;van Nguyen et al, 2018). However, what missing from this debate is a discussion about the policy of allocating the education budget for persons with disabilities of the total education budget available.…”
Section: Introductionmentioning
confidence: 99%
“…It also functions as one of the implementations of education that respect the differences, variety, and humanism to all students with a physical, emotional, mental, and social disability. They have potential intelligence or exceptional talent to receive a good education based on their need and ability (Wibowo & Muin, 2018).…”
Section: Introductionmentioning
confidence: 99%